Effectiveness of Learning Devices Based on Conceptual Change Model to Improve Concept Mastery of Students in the Gas Kinetic Theory Material - Susilawati Susilawati; Baiq Arum Kusumayati; Sutrio Sutrio; Aris Doyan (Pascasarjana, Mataram University, 2022)
This study aims to determine the effectiveness of learning devices based on conceptual change model to improve concept mastery of students in the gas kinetic theory material. The learning device was developed with a 4D model which includes the stages of define, design, develop, and disseminate. The tools developed are syllabus, lesson plans, student worksheets, and concept mastery test instruments. The research data was obtained from the results of a limited trial of 27 students of eleventh-grade MIPA 1 at SMAN 1 Kediri. The data analysis technique used in this research is data analysis using n-gain. Based on the results of the n-gain analysis, a score of 0.60 was obtained in the medium category for all students. The n-gain analysis of each student resulted in 18.51% of students experiencing a high level of concept mastery, 70.37% of students experiencing a moderate level of concept mastery, and 11.11% of students experiencing a level of mastery with low criteria. These results indicate that the learning devices based on the conceptual change model are effective to improve concept mastery of students in the gas kinetic theory material